2015
DOI: 10.1097/01.ewx.0000458827.76312.7f
|View full text |Cite
|
Sign up to set email alerts
|

Microneedling system alone versus microneedling system with trichloroacetic acid in the management of abdominal striae rubra

Abstract: BackgroundStriae distensae or stretch marks, although not a health risk, are of significant cosmetic concern as it affects the patient's psychological condition. Although many treatment modalities have been attempted with variable results, there is no standard treatment modality for it. Objective To compare the efficacy of a microneedling system (dermaroller) when used alone or combined with 15-30% trichloroacetic acid (TCA) in the management of striae rubra. Patients and methodsThis clinical trial included 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…This study also showed that there is more improvement in striae in Group II compared with Group I as 19 (63.3%) patients in Group II showed good to excellent response whilst only 10 (33.3%) patients in Group I demonstrated this. Meanwhile, skin biopsies taken from Group I at the follow-up session showed increase in collagen fibre content only, whilst Group II showed significant increase in epidermal thickness (P=0.005) and collagen fibre content [5].…”
Section: Abdominal Striaementioning
confidence: 92%
See 2 more Smart Citations
“…This study also showed that there is more improvement in striae in Group II compared with Group I as 19 (63.3%) patients in Group II showed good to excellent response whilst only 10 (33.3%) patients in Group I demonstrated this. Meanwhile, skin biopsies taken from Group I at the follow-up session showed increase in collagen fibre content only, whilst Group II showed significant increase in epidermal thickness (P=0.005) and collagen fibre content [5].…”
Section: Abdominal Striaementioning
confidence: 92%
“…However, it is noted that most studies have small sample sizes and are comparative prospective or pilot studies. Furthermore, some studies reviewed in this paper assessed efficacy of treatment on the same patient with split body areas receiving different treatments [5,11]. This can lead to bias when patient record their overall satisfaction, thus, not giving an accurate assessment of satisfaction as patients are more likely to be more satisfied with the area that had more treatment done.…”
Section: Microneedling and Needlingmentioning
confidence: 99%
See 1 more Smart Citation